Effect of a 4-week Nordic walking training on the physical fitness and self-assessment of the quality of health of women of the perimenopausal age - Saulicz, Mariola; Saulicz, Edward; Myśliwiec, Andrzej; Wolny, Tomasz; Linek, Paweł; Knapik, Andrzej; Rottermund, Jerzy (Menopause Review/Przegląd Menopauzalny, 2015)
Aim of the study: To determine the effect of a 4-week Nordic walking training on the physical fitness of women of the perimenopausal age and self-assessment of the quality of their health. Material and methods: Eighty-four women between 48 and 58 years of age were included in the study. Half of the group (42) was assigned to the control group and the other half was assigned to the experimental group. In both groups studied, physical fitness was evaluated using a modified Fullerton’s test and a quality of life self-assessment SF-36 (Short Form of Health Status Questionnaire). Similar tests were repeated 4 weeks later. In the experimental group, a Nordic walking training was conducted between the two tests. During 4 weeks, 10 training sessions were performed, each session was 60 minutes long, and there was an interval of 2 days between the sessions. Results: A 4-week Nordic walking training resulted in a significant improvement (p < 0.001) of physical fitness as demonstrated by an increased strength and flexibility of the upper and lower part of the body and the ability to walk a longer distance during a 6-minute walking test. Women participating in the training also showed a significant improvement in health in terms of both physical health (p < 0.001) and mental health (p < 0.001). Conclusions: A 4-week Nordic walking training has a positive effect on the physical fitness of the women in the perimenopausal age. Participation in training contributes also to a clearly higher self-assessment of the quality of health.